Is Emotional Intelligence an essential element in global learning environment to become socially responsible innovators? - Navaneedhan, Cittoor Girija; Kamalanabhan, TJ (Technium Social Sciences Journal, 2021)
Emotional intelligence in its basic sense is defined as the term representing the ability of an individual to understand his/her own emotions as well as others. 21st century is considered globally as knowledge-based society by eminent scholars, policy makers, stake holders etc, the question still remains unanswered is 1. Have we achieved 100% literacy rate globally? 2. Is there a sustainable development in global Economy? 3. Is there an Economic and Social narrow down between developed and developing nations of the world in terms of Education, Health, Industrialization? The inventions in 20th century contributed to a large extent providing material comfort to both developed and developing nations without addressing the emotional well-being of its citizens the core constituents of human capital. Therefore, the present-day global learning environment is expected to refine the emotional intelligence trait of teachers, the key players in shaping the society to a well-equipped emotionally successful global innovator.